SiGe W-CDMA transmitter for mobile terminal application. - Malhi, D.S (IEEE Journal of solid state circuits)
This paper presents the design considerations and experimental results of a transmitter integrated circuit (IC) for wide-band code division multiple access (W-CDMA) mobile terminal application based on a superheterodyne architecture. Implemented by utilizing IBM's 0.5-μm SiGe BiCMOS technology, the transmitter IC consumes approximately 270 mW with a 3.0-V power supply. The radio-frequency IC features a third-order output intercept point (OIP3) of +25.0 dBm, a 95-dB dynamic range, and 6.3% error vector magnitude.